Perancangan Sistem Mppt Untuk Dua Turbin Angin Kapasitas 300 Watt Pada Kondisi Kecepatan Angin Rendah Menggunakan Metode Perturb & Observe (P&O) - Muhammad Fadli Arief; Akhmad Musafa (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
In this research modeled design MPPT system for two wind turbines at low wind speed conditions using the method Perturb & Observe. This method is used to find the maximum power value of the system of two wind turbines that have been designed. The design has been created in simulation using the MATLAB software by utilizing the Simulink facility, consisting of modelling two wind turbines with a Permanent Magnet Synchronous Generator (PMSG), rectifier, Buck boost converter, and two Wind turbine with MPPT P&O. The simulation is done with the varying wind speeds gained at the time of testing the wind energy potential at the Universitas Budi Luhur area Rooftop Unit 7 floor 6, with varying resistive loads. Simulated results show that testing two wind turbines without MPPT can produce an output power of 1.05 watts and for a system of two wind turbines with MPPT generating a output power of 7.17 watts. In the condition of wind speed of 5.4 m/s for the load value varies from 5 ohm to 30 ohm, average difference in voltage, current and power between systems without MPPT and system with MPPT is 6.28 volts, 0.45 ampere and 5.22 watt.